Audits or Distortions: The Optimal Scheme to Enforce Self-Employment Income Taxes - Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2011)
I investigate the optimal auditing scheme for a revenue-maximizing tax-collection agency that observes not only reported pro ts, but also the level of employment at each firm. Each firm is owned by a single entrepreneur whose managerial ability is random. The optimal auditing scheme is discontinuous and non-monotone in ability. In intermediate audit costs, less-productive entrepreneurs face auditing probabilities that increase in ability, whereas the ablest ones are not audited. Finally, the effecive tax rate is higher in the middle of the managerial ability distribution; thus, the overall regressive (or progressive) bias that arises from evasion is unknown.
Keywords: D21; H26; K42; 330